ANALISIS FAKTOR PERSEPSI AKADEMISI TERHADAP PENGGUNAAN BUSANA ADAT DI LINGKUNGAN SEKOLAH - HARINI, LUH PUTU IDA; SARI, KARTIKA; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 10 No 3 (2021), 2021)
Traditional Balinese clothing is a typical Balinese clothing that is characterized by Balinese customs used as a form of cultural protection that reflects the nature of politeness, shade, peace, and pride for the wearer. The Governor of Bali in the Regulation of the Governor of Bali Number 79 of 2018, concerning the Day for the Use of Balinese Traditional Clothing states that one of the objectives of using Balinese traditional clothing is to maintain and maintain the preservation of Balinese Traditional Clothing in order to strengthen identity, character and character, to recognize the values the aesthetic, ethical, moral, and spiritual values ??contained in Balinese culture and encourage increased use of local Balinese fashion products and industries. The purpose of this study was to determine the factors that influence academic perceptions of the use of traditional clothing in the school environment. This research was conducted in high schools in Denpasar, using the factor analysis method. The sample in this study were 181 respondents. The sampling technique used was purposive sampling. The results showed that the factors that influenced students' perceptions of the use of traditional clothing in the school environment were comfort in traditional clothing, knowledge of the rules of traditional dress, knowledge of traditional clothing, ethics of Balinese traditional dress and tourists and Balinese traditional clothing. These five factors can explain the diversity of students 'perceptions of 58.742 percent, with the dominant factor affecting students' perceptions of the use of traditional clothing in the school environment is comfort in traditional dress.